Formation of prices for scientific and technical products of south - Kobielieva, T. O.; Pererva, P. G.; Klymentova, M. V. (Видавничий дім "Києво-Могилянська академія", 2023)
It has been proven that the price forms the economic effect of using a scientific and technical product. This is the difference between the result (income) that will be received for the entire regulatory term of using a new tool or technology, and the costs of their development and production. and application. Moreover, the calculation is carried out for each year with subsequent reduction of the annual economic effect to the initial period (year).
Формування цін на науково-технічну продукцію півдня
Keywords: price; cost price; scientific and technical products; intellectual property; production